Investigation of gender differences in familiar portfolio choice - Maknickienė, Nijolė; Rapkevičiūtė, Lina (Journal of Business Economics and Management, 2022)
The prevailing assumption holds that investors include in their portfolios securities that they know well, are located near their place of residence, or align with their fields of interest. This article analyse familiarity in investment through gender perspective and their fields of interest. Women and men field of interest is defined by enabling online magazines’ article’s themes. The aim of this paper is to investigate gender-based behavioural differences in investment decisions – i.e. to define women’s and men’s fields of interests and value investment portfolios. Portfolios differ according to whether they are formed from securities that are consistent with women’s fields of interest, men’s fields of interest or both women’s and men’s fields of interest. Textual analysis was employed to identify men’s and women’s fields of interest. Investment portfolios were built using mean variance (MV) and Black–Litterman (BL) models. The analysis revealed that portfolios built from men’s fields of interests are more diversified than are portfolios built either from women’s fields of interests or from both men’s and women’s fields of interest. Analysing 12 portfolios’ efficiency revealed that women’s portfolio returns are more stable than are men’s. Moreover, the study demonstrated that time impacts investment portfolio returns to a greater extent than do gendered fields of interest. The article complements the existing knowledge about bias in investor familiarity, which results from differences in men’s and women’s fields of interest.